2022
DOI: 10.1002/ame2.12226
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacological prediction and molecular docking analysis of the combination of Atractylodes macrocephala Koidz. and Paeonia lactiflora Pall. in the treatment of functional constipation and its verification

Abstract: Background We aimed to reveal the mechanism of functional constipation in the treatment of Atractylodes macrocephala Koidz. (AMK) and Paeonia lactiflora Pall. (PLP). Methods The main active ingredients of AMK and PLP were screened by the Traditional Chinese Medicine Systems Pharmacology (TCMSP) platform. A database of functional constipation targets was established by GeneCard and OMIM. An “ingredient‐target” network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…Of note, suppression of AQP3 function in the colon results in diarrhoea (52). FC mice show increased levels of AQP3 and AQP9 compared with those in controls, which is consistent with the present results (56). Here, loperamide-induced elevation in AQP3 and AQP9 were decreased by Arc treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, suppression of AQP3 function in the colon results in diarrhoea (52). FC mice show increased levels of AQP3 and AQP9 compared with those in controls, which is consistent with the present results (56). Here, loperamide-induced elevation in AQP3 and AQP9 were decreased by Arc treatment.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Painong San, a Chinese herbal compound for the treatment of colitis, increased the expression of MUC2 protein in the colon, 27 and P. lactiflora downregulated the expression level of AQP3 in the colon of constipated rats. 28 Our study also showed that PF significantly increased MUC2 protein expression and the number of colonic goblet cells and decreased AQP3 protein expression in CDiph-induced STC rats, thereby improving intestinal fluid metabolism disorders.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have shown that BZBS can treat FC by regulating aquaporins. 18 In this study, we explored another underlying mechanism of BZBS on FC rats induced by diphenoxylate, and provide a more theoretical basis for the clinical treatment of FC by BZBS. University, Hangzhou, China).…”
Section: Introductionmentioning
confidence: 99%
“…At present, studies of the BZBS herb pair have focused on intestinal stress syndrome and less attention has been paid to FC. Previous studies have shown that BZBS can treat FC by regulating aquaporins 18 . In this study, we explored another underlying mechanism of BZBS on FC rats induced by diphenoxylate, and provide a more theoretical basis for the clinical treatment of FC by BZBS.…”
Section: Introductionmentioning
confidence: 99%